Gambaran Sanitasi Lingkungan Pasar dan Tingkat Kepadatan Lalat di Pasar Inpres Larantuka, Kecamatan Larantuka, Kabupaten Flores Timur - Agnes Kewa Hayon; Mustakim Sahdan; Cathrin W.D. Geghi (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Market environment sanitation is an effort to monitor, prevent, control and control everything in the market environment such as flies. The density of flies can increase if the environment is dirty, for example markets that do not meet market environmental sanitation requirements such as rubbish dumps, waste water drainage channels and adequate water supplies. The aim of this research is to determine the description of environmental sanitation conditions and the density of flies at the Larantuka Inpres Market, Larantuka District, East Flores Regency. The type of research used is descriptive observation. The samples used in this research were all market sanitation facilities or facilities. The data obtained was then analyzed descriptively. The results of the research show that the results of the environmental sanitation conditions of the Larantuka Inpres Market based on the results of calculating the assessment variables on the external supervision observation sheet for environmental health inspections are categorized as not meeting the requirements for a healthy market (57.5%). The level of fly density at the Larantuka Inpres Market based on the results of measurements and calculations was obtained. 7 birds/blockgrill with a high density category of flies, it is necessary to secure the fly breeding places and if possible plan control measures. Therefore, it is necessary to collaborate between the government and local communities, including traders, market managers and district health services, to pay attention to the cleanliness of the market environment.